A Multifunctional Radiated Patterned Surface for Fog Collection, Oil/Water Separation, and Interfacial Floatability. Issue 24 (24th July 2022) - Song, Yun‐Yun; Zhang, Zhong‐Qiang; Cheng, Guang‐Gui; Liu, Yan; Ding, Jian‐Ning
Abstract: Multifunctional patterned surfaces with special wettability appeal to many researchers because of their potential applications in fog collection, microfluidics, and medical devices. To realize these functions and extend the corresponding application scopes, this article reports a multifunctional superhydrophobic radiated pattern on different wetting surfaces. Intriguingly, the hydrophilic surface with radiated pattern can quickly drive tiny water droplets toward more wetting regions, where water droplets move from center to the edge of a circle with a fog collection rate of about 3.075 g cm −2 h. However, the superhydrophobic surface with the radiated pattern triggers water to move from the edge to the center of a circle and achieves reverse transport. Importantly, the superhydrophobic surface can absorb oil and act as a micro‐reactor to realize oil/water separation. The surface can be transformed to be superhydrophilic by oxygen plasma etching and then recovers the superhydrophobicity by laser etching, which convinces the excellent restoration capacity. Furthermore, the surface composed of a superhydrophobic upper surface and a hydrophobic lower surface shows improved interfacial floatability. The findings offer a novel insight into the design of a multifunctional surface that not only enhances the fog collection but also realizes reverse liquid transport, and oil/water separation. Abstract : A superhydrophobic radiated pattern on different wetting surfaces is successfully designed. The hydrophilic surface can realize efficient fog collection. The superhydrophobic surface achieves reverse liquid transport and oil/water separation. The surface can be transformed to be superhydrophilic by oxygen plasma etching and recover superhydrophobicity by laser etching, which convinces the restoration capacity. Furthermore, the surface shows improved interfacial floatability.